(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This article presents the findings of scientific research conducted on the distribution and damage levels of the most harmful pests affecting winter wheat crops in the Syrdarya region of Uzbekistan. The study focuses on the pests Eurygaster integriceps, Oulema melanopus, Haplothrips tritici, and Schizaphis graminum, assessing their infestation rates and economic impact. Furthermore, the research explores the biological control measures aimed at mitigating their harmful effects and enhancing crop protection strategies.